Iglesia católica - García Pazmiño, Luis Alejandro (2016)
The University of Las Americas (UDLA) make an agreement with the Municipality of the town of Francisco de Orellana (El Coca). Francisco de Orellana is located in the northwest of Ecuador and has shown a really fast growth generated mainly by oil exploitation. On the other hand this city has a clear deficit of public spaces and especially green areas, thus being contradictory to the city because this is located in the Amazon region where the lush vegetation, rich biodiversity, variety of cultures, looks affected by the rapid growth of it. For this reason, it is intended to perform a Urban Management Plan for the city, generating a research process so that the city can function more effectively. This approach born urban and architectural projects that will help provide alternatives to meet the current and future needs of the industry and above, recognizing their potential and problems. In the diagnosis made in the city of Coca, due to its nature, it is proposed to generate an idea of the city that is developed by several self centralidades, forming a membrane exchange that encourages social, economic, cultural development and environmental. For this reason, the development of a Catholic Church in conjunction with the design of a public park. The project is proposed as an element of neutrality, whose function is to cover the deficit of religious facilities in the central part of the city and connection between two centralidades (Administrative and Technology). The project has been propose as a neutral and inclusive element; It is included with a character of community development, and collective space; to be claimed as a social and urban event. Finally its functionality as a spatial element of interconnection, articulation and intertwining the aforementioned centralidades and commercial corridor.